2019
DOI: 10.1111/1756-185x.13745
|View full text |Cite
|
Sign up to set email alerts
|

Identifying damage clusters in patients with systemic lupus erythematosus

Abstract: Aim Systemic lupus erythematosus (SLE) causes irreversible damage to organ systems. Recently, evidence has been obtained for subphenotypes of SLE. This study aimed to identify damage clusters and compare the associated clinical manifestations, SLE disease activity, mortality, and genetic risk scores (GRS). Methods The study was conducted on the Hanyang BAE lupus cohort. Patients with disease duration <5 years were excluded to minimize confounding effects of disease duration. They were grouped into 3 clusters b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…A cohort of Spanish patients with SLE showed that cardiovascular and musculoskeletal damage among several damage patterns was correlated with mortality [28]. An identification of three clusters using the damage index scale concluded that the cluster with prevalent renal and ocular damage had the highest damage score [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort of Spanish patients with SLE showed that cardiovascular and musculoskeletal damage among several damage patterns was correlated with mortality [28]. An identification of three clusters using the damage index scale concluded that the cluster with prevalent renal and ocular damage had the highest damage score [19].…”
Section: Discussionmentioning
confidence: 99%
“…These tools that identify disease activity could be used to classify patients with SLE, and such differentiation could help modify further treatment to prevent clinical worsening. Several attempts have been made to classify patients based on clinical or immunological data, suggesting different phenotypes of SLE [17][18][19]. The formulation of classified subtypes through more sophisticated statistical methods can help assess and manage the disease and educate patients with mixed symptoms.…”
Section: Of 11mentioning
confidence: 99%
“…Cluster analysis revealed the co-appearance of ocular and renal damages ( 76 ). Two pertinent studies indicated that patients with both renal and ocular damage were more likely to be categorized into the same cluster with the highest risk of mortality and the highest disease activity ( 77 , 78 ). In addition, in patients with SLE, researchers noted significant associations between both renal and ocular damage and thrombocytopenia in patients with SLE ( 79 ).…”
Section: Associations Between Ocular Fundus and Other Systemic Involv...mentioning
confidence: 99%
“…As a common rheumatic immune disease, systemic lupus erythematosus (SLE) is a chronic autoimmune disease that usually affects women in their reproductive years. Its clinical manifestations are complex and variable; it can involve the production of a large number of autoantibodies and can affect important organs, such as the cardiovascular system, the nervous system, the kidneys, and the lungs, 1 which can even be life‐threatening. In recent years, cohort studies of SLE patients in low‐ and middle‐income have found neuropsychiatric lupus, infection, and disease activity as the main causes of death in 1 to 3 year survival, 2 and renal failure, pulmonary hypertension, and cardiovascular disease (CVD) as the main causes of late death.…”
mentioning
confidence: 99%